ROLE OF VITAMIN D ON ANTI-MULLERIAN HORMONE (AMH) AND POLYMORPHISM OF AMHR II IN INFERTILITY: A REVIEW - ANJUM, ASRA; KUMAR, B. SENTHIL (International Journal of Applied Pharmaceutics, 2022)
Deficiency of vitamin D3 has become common in both developed and developing countries. Vitamin D receptors are found on the granulosa cells of ovarian tissue and its deficiency plays a role in ovarian dysfunction. Anti Mullerian Hormone (AMH) is generated in the small and growing follicles of ovaries by the granulosa cells. Serum AMH is one of the marker for ovarian reserve. We reviewed the current literature on Vitamin D3 and AMH in present clinical practice. There is a relationship between vitamin D3 and Anti-Mullerian Hormone, which exists at serum as well as genetic level. The AMH gene promoter has vitamin-D responsive elements, which gives the research-based evidence that AMH gene expression is effected by Vitamin D3. This systematical review is done to assess and encapsulate the available proof concerning the correlation between vitamin D3 and AMH and its type II receptor (AMHR II) functioning.